Film history : an introduction - Thompson, Kristin, 1950-; Bordwell, David; Smith, Jeff, 1962 December 17- (New York McGraw Hill, 2022)
"Around the world, at any instant, millions of people are watching movies. They watch mainstream entertainment, serious "art films," documentaries, cartoons, experimental films, educational shorts. They sit in air-conditioned theaters, in village squares, in art museums, in college classrooms, in their homes before a television screen, in coffee shops before a computer monitor or cell-phone screen. The world's movie theaters sell 8 billion tickets each year. With the availability of films on video-whether broadcast, fed from cable or satellites or the Internet, or played back from disc or digital file-the audience has multiplied far beyond that. Nobody needs to be convinced that film has been one of the most influential media of the past hundred years. Not only can you recall your most exciting or tearful moments at the movies, you can also probably remember moments in ordinary life when you tried to be as graceful, as selfless, as tough, or as compassionate as those larger-than-life figures on the screen. The way we dress and cut our hair, the way we talk and act, the things we believe or doubt-all these aspects of our lives are shaped by films. Films also provide us with powerful artistic experiences, insights into diverse cultures, and new ways of thinking"--
Includes bibliographical references and index.
Keywords: Motion pictures -- History